Experience of Trauma and PTSD Symptoms in Autistic Adults: Risk of PTSD Development Following DSM‐5 and Non‐DSM‐5 Traumatic Life Events. Issue 12 (22nd April 2020) - Rumball, Freya; Happé, Francesca; Grey, Nick
Abstract : Research to date suggests that individuals with autistic spectrum disorder (ASD) may be at increased risk of developing post‐traumatic stress disorder (PTSD) following exposure to traumatic life events. It has been posited that characteristics of ASD may affect perceptions of trauma, with a wider range of life events acting as possible catalysts for PTSD development. This study set out to explore the nature of "trauma" for adults with ASD and the rates of self‐reported PTSD symptomatology following DSM‐5 and non‐DSM‐5 traumas—the latter being defined as those that would not meet the standard DSM‐5 PTSD trauma Criterion A. Fifty‐nine adults with ASD who reported exposure to traumatic events took part in the study, which involved completing a series of online questionnaires. Thirty‐three individuals reported experiencing a "DSM‐5" traumatic event (i.e., an event meeting DSM‐5 PTSD Criterion A) and 35 reported a "non‐DSM‐5" traumautic event. Trauma‐exposed ASD adults were found to be at increased risk of PTSD development, compared to previous general population statistics, with PTSD symptom scores crossing thresholds suggestive of probable PTSD diagnosis for more than 40% of ASD individuals following DSM‐5 or non‐DSM‐5 traumas. A broader range of life events appear to be experienced as traumatic and may act as a catalyst for PTSD development in adults with ASD. Assessment of trauma and PTSD symptomatology should consider possible non‐DSM‐5 traumas in this population, and PTSD diagnosis and treatment should not be withheld simply due to the atypicality of the experienced traumatic event. Lay Summary: This study explored the experience of trauma and rates of probable post‐traumatic stress disorder (PTSD) in adults with autistic spectrum disorder (ASD). We asked 59 autistic adults to complete online questionnaires about their experiences of stressful or traumatic events and related mental health difficulties. Autistic adults experienced a wide range of life events as traumatic, with over 40% showing probable PTSD within the last month and over 60% reporting probable PTSD at some point in their lifetime. Many of the life events experienced as traumas would not be recognized in some current diagnostic systems, raising concerns that autistic people may not receive the help they need for likely PTSD.